2016
DOI: 10.1093/toxsci/kfw203
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs: A Novel Paradigm for Toxicology

Abstract: Long non-coding RNAs (lncRNAs) are over 200 nucleotides in length and are transcribed from the mammalian genome in a tissue-specific and developmentally regulated pattern. There is growing recognition that lncRNAs are novel biomarkers and/or key regulators of toxicological responses in humans and animal models. Lacking protein-coding capacity, the numerous types of lncRNAs possess a myriad of transcriptional regulatory functions that include cis and trans gene expression, transcription factor activity, chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 171 publications
1
68
0
Order By: Relevance
“…Emerging evidences and researches have demonstrated that the dysregulated expression of long noncoding RNAs (lncRNAs) play important roles in human cancers (Chandra Gupta & Nandan Tripathi, ). LncRNAs are type of non‐coding RNA transcribed from corresponding gene locus with more than 200 nucleotide length (Dempsey & Cui, ). LncRNAs epigenetically modulate biological functions of physiological and pathological activity via transcriptional and post‐transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidences and researches have demonstrated that the dysregulated expression of long noncoding RNAs (lncRNAs) play important roles in human cancers (Chandra Gupta & Nandan Tripathi, ). LncRNAs are type of non‐coding RNA transcribed from corresponding gene locus with more than 200 nucleotide length (Dempsey & Cui, ). LncRNAs epigenetically modulate biological functions of physiological and pathological activity via transcriptional and post‐transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…CAR ChIP-Seq experiments are challenging because of a lack of a good antibodytargeting endogenous CAR protein, although one could overcome this dmd.aspetjournals.org technical challenge using an adenovirus-based system to direct the expression of YFP-CAR fusion constructs in transgenic mice (Niu et al, 2018); however, it seems reasonable to speculate that a substantial number of differentially regulated intergenic lncRNAs by TCPOBOP may be a result of direct CAR-binding to the intergenic regions. Lastly, lncRNAs produced from the 39-UTR regions relative to PCGs may be important in protecting the mRNAs from miRNA-mediated degradation and/or inhibition of protein synthesis (Karapetyan et al, 2013;Dempsey and Cui, 2017). Although lncRNAs produced in distal regions may migrate to the 39-UTRs of PCGs and perform similar functions, the local production of lncRNAs may have a special advantage in this process.…”
Section: Discussionmentioning
confidence: 99%
“…According to the ENCODE Project, lncRNAs represent approximately 80% of functional sequences in the human DNA and are the predominant nonribosomal and nonmitochondrial RNA species in human cells (Kapranov et al, 2010;ENCODE Project Consortium, 2012). LncRNAs transcribed proximally or distally to protein-coding genes (PCGs) can modulate a wide spectrum of biologic events, including chromatin epigenetic remodeling, transcription factor assembly, alternative splicing, mRNA stability, and protein translation efficiency (Geisler and Coller, 2013;Karlsson and Baccarelli, 2016;Dempsey and Cui, 2017). Growing evidence in the literature suggests that lncRNAs are novel biomarkers and/or key contributors during physiologic, pharmacologic, and toxicologic responses, including complex human diseases, developmental disorders, as well as xenobioticinduced adverse outcomes (Dempsey and Cui, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to them is associated with the etiology of diseases. LncRNAs play critical roles in these processes (Dempsey & Cui, 2017;Karlsson & Baccarelli, 2016). The roles of lncRNAs in the toxicology of ECs receive great attention and are being investigated (Aigner et al, 2016).…”
Section: Roles Of Long Non-coding Rna In the Health Impact Of Envirmentioning
confidence: 99%